2022
DOI: 10.3390/s22041612
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Shape of the Forces Applied on the Foot Rest and Paddle by Elite Kayakers

Abstract: The study aimed to investigate the magnitude and shape of the forces applied on the foot rest, foot strap, and paddle. Thirteen elite male kayakers participated in this study and performed a 2-min test simulating 500 m race pace in a kayak ergometer. Forces applied by the kayakers on the paddle, foot rest, and foot strap were measured with load cells and recorded by an electronic measuring system. The magnitude of the peak forces applied on the foot rest (left: 543.27 ± 85.93; right: 524.39 ± 88.36) approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Resistance strain load cell is a kind of mechanical measurement sensor which is wildly used in various field such as industrial robotics [1,2], agriculture [3][4][5], medicine [6][7][8][9], sports industry [10,11], and many high-precision weighing applications [12][13][14][15][16][17]. It is a sensitive component that converts the deformation of the strain gage under force into an electrical signal [18].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance strain load cell is a kind of mechanical measurement sensor which is wildly used in various field such as industrial robotics [1,2], agriculture [3][4][5], medicine [6][7][8][9], sports industry [10,11], and many high-precision weighing applications [12][13][14][15][16][17]. It is a sensitive component that converts the deformation of the strain gage under force into an electrical signal [18].…”
Section: Introductionmentioning
confidence: 99%
“…Papers [ 7 , 8 ] both studied kayaking. The aim of [ 7 ] was to investigate the magnitude and shape of the forces applied on the foot rest, foot strap, and paddle, and it was found that when comparing the best and worst kayakers’ performance, the best showed greater magnitudes of force and greater synchronization of the peak forces.…”
mentioning
confidence: 99%
“…Papers [ 7 , 8 ] both studied kayaking. The aim of [ 7 ] was to investigate the magnitude and shape of the forces applied on the foot rest, foot strap, and paddle, and it was found that when comparing the best and worst kayakers’ performance, the best showed greater magnitudes of force and greater synchronization of the peak forces. It was recommended that analyses of the force–time curves, including not only the forces applied by the kayaker on the paddle but also the ones applied on the foot rest and strap, should be considered relevant in terms of technique analyses.…”
mentioning
confidence: 99%
“…Papers [7] and [8] both studied kayaking. The aim of [7] was to investigate the magnitude and shape of the forces applied on the foot rest, foot strap, and paddle, and it was found that when comparing the best and worst kayakers' performance, the best showed greater magnitudes of force and greater synchronization of the peak forces.…”
mentioning
confidence: 99%
“…Papers [7] and [8] both studied kayaking. The aim of [7] was to investigate the magnitude and shape of the forces applied on the foot rest, foot strap, and paddle, and it was found that when comparing the best and worst kayakers' performance, the best showed greater magnitudes of force and greater synchronization of the peak forces. It was recommended that analyses of the force-time curves, including not only the forces applied by the kayaker on the paddle but also the ones applied on the foot rest and strap, should be considered relevant in terms of technique analyses.…”
mentioning
confidence: 99%